The effect of fear of missing out and scarcity marketing on impulse buying of thrift consumers with the mediation of purchase intention: A study on generation Z in Garut City - Mohamad Rafie Eka Putra; Wati Susilawati (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to examine the influence of Fear of Missing Out (FOMO) and scarcity marketing on impulse buying among Generation Z thrifting consumers in Garut City, with purchase intention as a mediating variable. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) based on data collected from 162 Generation Z respondents who had purchased thrift products more than three times. The study investigates consumer behavior in the one-of-a-kind thrifting market following Indonesia’s ban on imported used clothing, providing evidence on the mediating role of purchase intention in explaining consumers’ responses to perceived scarcity. The results indicate that FOMO does not have a significant direct effect on impulse buying, whereas scarcity marketing has a positive and significant effect. Both FOMO and scarcity marketing positively influence purchase intention, which in turn significantly affects impulse buying and mediates the relationships between the two antecedent variables and impulsive purchasing behavior. These findings extend the understanding of consumer behavior in scarcity-driven retail environments and highlight the pivotal role of purchase intention in translating psychological and marketing stimuli into impulse buying. The study also provides practical implications for thrifting businesses by emphasizing the importance of effective scarcity marketing, transparent product information, and social media engagement to strengthen consumer interest and encourage sustainable purchasing behavior. Keywords: Fear Of Missing Out; Scarcity Marketing; Impulse Buying; Purchase Intention; Generation Z